Clinical symptoms of acute appendicitis correlating to its intraoperative anatomical position - Chandan Singh; Aamina Hamdule; Amey Kasbekar; Shishir Kamble (Al Ameen Journal of Medical Sciences)
Background: Acute appendicitis is a common surgical emergency that can cause a variety of clinical symptoms, which are frequently impacted by the anatomical location of the inflamed appendix. The precise localisation of the appendix is critical for timely diagnosis and therapy. Objectives: The purpose of this study was to look at the relationship between clinical symptoms of acute appendicitis and the appendix's anatomical position during surgery. Furthermore, it assessed the diagnostic accuracy of clinical examination and ultrasound in determining the appendix's position. Methods: This prospective, observational study was carried out over a one-year period at a tertiary care centre in Navi Mumbai. Patients who presented with acute appendicitis were included. The clinical symptoms, ultrasound results, and intraoperative anatomical locations of the appendix were documented. A statistical analysis was conducted to determine the relationship between clinical symptoms, imaging findings, and appendix positions. Results: A total of 70 patients with acute appendicitis were included in the study. The most common anatomical position of the appendix was retrocecal (78.4%), followed by pelvic (19.6%) and pre-ileal (2%) positions. Clinical examination showed high sensitivity (100%) but lower specificity (63.64%) for detecting retrocecal appendicitis and lower sensitivity (63.64%) but perfect specificity (100%) for pelvic appendicitis. Ultrasonography demonstrated high sensitivity (100%) for retrocecal appendicitis but low sensitivity (27.3%) for pelvic appendicitis. Conclusions: The clinical appearance of acute appendicitis varies according to the anatomical position of the appendix. Clinical examination and ultrasonography have limits in precisely establishing the position of the appendix, highlighting the importance of an integrated strategy that combines clinical, radiological, and operational findings for exact diagnosis and management.